2018
DOI: 10.3390/ani8080133
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Blood Analysis with Feed Efficiency and Developmental Stage in Grass-Fed Beef Heifers

Abstract: Simple SummaryIndividual cattle of identical developmental stage vary in their efficiency of feed utilization to achieve a similar productive performance in terms of growth rate and body composition upon accounting for breed, age and gestation stage. Technical issues to measure individual feed intake on the farm limits the identification of feed-efficient cattle. This creates a demand for indirect approaches to infer feed efficiency, such as blood parameters. Our study revealed differences in blood parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
2
6
1
Order By: Relevance
“…Total protein and albumin were observed to have a significant positive correlation ( p < 0.05) with FCE, while albumin was correlated only with ADG. Triiodothyronin (T 3 ), a growth moderator, and thyroxin (T 4 ) showed a negative correlation with ADG, with its optimum level in circulation in efficiently feed-utilizing heifers, which corroborates with an earlier study ( 10 ). A significant positive correlation of LDH and SGOT with FCE indicates that feed utilization is an energy-dependent function, which requires higher reducing power for optimum productivity of the animal.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Total protein and albumin were observed to have a significant positive correlation ( p < 0.05) with FCE, while albumin was correlated only with ADG. Triiodothyronin (T 3 ), a growth moderator, and thyroxin (T 4 ) showed a negative correlation with ADG, with its optimum level in circulation in efficiently feed-utilizing heifers, which corroborates with an earlier study ( 10 ). A significant positive correlation of LDH and SGOT with FCE indicates that feed utilization is an energy-dependent function, which requires higher reducing power for optimum productivity of the animal.…”
Section: Resultssupporting
confidence: 90%
“…A thorough study of all possible processes related to this variation, if it does not lead to an efficient early selection, at least would be useful for deducing genotypes selectively for RFI/FCE. Blood metabolic markers associated with feed conversion efficiency were earlier used to enhance profitability ( 7 , 8 ) of yearling beef bulls ( 9 ) and crossbred heifers ( 10 ), wherein the level of FCE was extrapolated on the scale of energy substrates as blood metabolite(s), i.e., glucose, triglycerides, urea, creatine phosphokinase as protein metabolite, total plasma protein, and aspartate aminotransferase, which in turn are influenced by the hypothalamus–pituitary–adrenal axis ( 11 , 12 ). Several types of potential proxies for RFI, using energy metabolism ( 13 ), hepatic mitochondrial function ( 14 ), and visceral organ metabolism ( 15 ), have been identified to monitor feed efficiency in other species.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding blood metabolites, negative RFI cows had higher cholesterol concentrations than positive RFI cows during lactation. These results differ from those reported by Cônsolo et al [27] who found lower plasma cholesterol levels in more efficient pregnant heifers, and by Wood et al [28] who related low and nonsignificant correlation between plasma cholesterol levels and RFI or RFI class of mature pregnant beef cows. Although there is evidence of a positive relationship between RFI and plasma cholesterol in growing animals of some species as mice, pigs [29] and cattle [30], this relation in mature beef cows are not clear.…”
Section: Plos Onecontrasting
confidence: 96%
“…Maintenance of blood calcium within the acceptable range of 8 to 10 mg/dl is a delicate balance between the demand for calcium for milk production and the homeostatic mechanisms of the cows to maintain blood calcium [32] (Fig 6). Cônsolo et al [27] reported a trend (P = 0.06) toward higher calcium concentrations in more efficient pregnant heifers. These authors found higher phosphorus levels in more efficient animals and suggested greater availability of phosphorus for growth and energy metabolism.…”
Section: Plos Onementioning
confidence: 96%
“…Therefore, heifers must be monitored throughout the rearing period to identify any deviations from pre-set rearing targets at an early stage [ 15 ]. Analysis of blood biochemistry is an indirect approach to infer the efficiency of replacement rearing of heifers [ 4 ].…”
mentioning
confidence: 99%